2010
DOI: 10.1063/1.3310012
|View full text |Cite
|
Sign up to set email alerts
|

Structural defects in LiCoO2 studied by L7i nuclear magnetic relaxation

Abstract: Microscopic environments and dynamics in LiCoO2 systems were probed by L7i nuclear magnetic relaxation measurements with regard to the structural defects as revealed by x-ray diffraction and electron spin resonance measurements. Thus, the structural defects of differing degrees, associated with Li vacancies, were well accounted for in the temperature-dependent spin-lattice relaxation rate analysis, and in the structural and dynamical inhomogeneity as derived from the relaxation patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We hypothesize that heterogeneously delithiating a single plane can induce a larger effect, than was previously calculated for homogeneous delithiation by Wu and Zhang . Results of Li NMR indicate that these point defects are heterogeneously distributed, suggesting that this hypothesis is reasonable. Calculations similar to those in Ref.…”
Section: Resultsmentioning
confidence: 48%
“…We hypothesize that heterogeneously delithiating a single plane can induce a larger effect, than was previously calculated for homogeneous delithiation by Wu and Zhang . Results of Li NMR indicate that these point defects are heterogeneously distributed, suggesting that this hypothesis is reasonable. Calculations similar to those in Ref.…”
Section: Resultsmentioning
confidence: 48%
“…Here, we compare the present LCO result with those for Na 1−y CoO 2 , which has a similar structure to that for LCO. Based on χ and 23 Na-NMR measurements on NaCoO 2 (NCO) [40], Co 3+ ions are reported to be a nonmagnetic S = 0 (t 6 2g ) state in the T range between ß25 and 300 K. This was confirmed by μSR [41]. Thus, the past data suggest the absence of nonordered magnetism or spin fluctuation in NaCoO 2 [40,41].…”
Section: Origin Of Nonordered Magnetism At Ambient Temperaturementioning
confidence: 84%
“…Although Artemenko et al [15] reported an EPR signal with g = 2.16 for VST-LCO, probably due to the Li + -O − PM centers; such an EPR signal is observed only below ß30 K with H pp 110 Oe. Kim et al [23] reported the EPR signal with g 2.16 at ambient temperature for the compound prepared by a molten salt method with x 0 = 7. However, their LCO compound is most likely quite different from a typical ST-LCO and OST-LCO based on their electrochemical data, such as a large hysteresis between the charge and discharge curve and a small Q dis value (<100 mAh•g −1 ) in the voltage range between 2.8 and 4.2 V [23].…”
Section: B Electron Paramagnetic Resonancementioning
confidence: 99%
“…Studies have shown that after plasma treatment of cancer cells, cytochrome c was released [ 20 ] and the expression of NOXA, [ 21 ] Bax, [ 22 ] caspase 9, [ 23 ] and caspase 3/7 [ 20,24–26 ] was increased. Additionally, loss of mitochondrial membrane potential [ 20,25,27–29 ] and induction of DNA fragmentation [ 30 ] after plasma treatment were observed in some studies. In summary, cancer cells treated by CAP follow DNA damage pathways [ 31,32 ] as well as apoptosis pathways.…”
Section: Introductionmentioning
confidence: 99%